Rebung / Afiq Maizan Ahmad Masrin, Nur Allanea Nylea Saiful Rizal and Azizah Md Ajis - Ahmad Masrin, Afiq Maizan; Saiful Rizal, Nur Allanea Nylea; Md Ajis, Azizah (2024)
This sculpture explores the metaphorical application of "rebung" (bamboo shoots) to illustrate Universiti Teknologi MARA (UiTM)’s mission of nurturing students from their formative stages into knowledgeable, resilient, and impactful individuals. By comparing the growth of bamboo, which requires careful nurturing in its early stages, to the educational journey at UiTM, the design emphasizes the importance of early guidance, holistic development, and sustainable practices in shaping future leaders. Rebung highlights UiTM’s commitment to excellence, sustainability, and cultural heritage, illustrating how the university shapes individuals to make a global impact while remaining rooted in tradition.